2018
DOI: 10.1200/jco.2018.77.8613
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial Comparing Intraperitoneal and Intravenous Paclitaxel Plus S-1 Versus Cisplatin Plus S-1 in Patients With Gastric Cancer With Peritoneal Metastasis: PHOENIX-GC Trial

Abstract: Purpose Intraperitoneal paclitaxel plus systemic chemotherapy demonstrated promising clinical effects in patients with gastric cancer with peritoneal metastasis. We aimed to verify its superiority over standard systemic chemotherapy in overall survival. Patients and Methods This randomized phase III trial enrolled patients with gastric cancer with peritoneal metastasis who had received no or short-term (< 2 months) chemotherapy. Patients were randomly assigned at a two-to-one ratio to receive intraperitoneal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
214
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(236 citation statements)
references
References 28 publications
4
214
2
2
Order By: Relevance
“…The 1-year OS rate was 71.5% (95% CI, 58-81%), the overall response rate was 67% (95% CI, 22-96%), and 75% of patients achieved disappearance of malignant cells on peritoneal cytology evaluation [11]. In addition, the results of a phase III trial comparing intraperitoneal and intravenous paclitaxel plus S-1 (IP arm) versus cisplatin plus S-1 (SP arm) in patients with gastric cancer with peritoneal metastasis (PHOENIX GC trial) were reported in 2018 [12]. This trial failed to show statistical superiority of intraperitoneal paclitaxel plus systemic chemotherapy possibly due to an unexpected imbalance that patients in the IP arm had significantly more ascites and the crossover from SP to IP.…”
Section: Discussionmentioning
confidence: 99%
“…The 1-year OS rate was 71.5% (95% CI, 58-81%), the overall response rate was 67% (95% CI, 22-96%), and 75% of patients achieved disappearance of malignant cells on peritoneal cytology evaluation [11]. In addition, the results of a phase III trial comparing intraperitoneal and intravenous paclitaxel plus S-1 (IP arm) versus cisplatin plus S-1 (SP arm) in patients with gastric cancer with peritoneal metastasis (PHOENIX GC trial) were reported in 2018 [12]. This trial failed to show statistical superiority of intraperitoneal paclitaxel plus systemic chemotherapy possibly due to an unexpected imbalance that patients in the IP arm had significantly more ascites and the crossover from SP to IP.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose paclitaxel changed macrophage phenotype from M2 to M1 through the toll-like receptor (TLR)-4, resulting in tumor growth inhibition [35,36]. This theory is consistent with taxan-containing therapies showing superior results than other regimens for treating gastric cancer [37,38]. Half of the patients with unresectable GC have PM at the time of second-line chemotherapy induction [2,38].…”
Section: Discussionmentioning
confidence: 61%
“…and i.v. paclitaxel plus S‐1 (IP) versus cisplatin plus S‐1 (SP) in patients with peritoneal metastasis . Although this trial failed to show statistical superiority of intraperitoneal paclitaxel plus systemic chemotherapy, the 3‐year overall survival rate was 21.9% (95% CI, 14.9%‐29.9%) in the IP arm and 6.0% (95% CI, 1.6%‐14.9%) in the SP arm.…”
Section: Therapeutic Strategies According To Macroscopic Classificatimentioning
confidence: 99%